2012
DOI: 10.1038/nprot.2012.038
|View full text |Cite
|
Sign up to set email alerts
|

A simple and rapid nonviral approach to efficiently transfect primary tissue–derived cells using polyethylenimine

Abstract: This protocol outlines steps for optimizing the transfection of adherent primary mammalian cells using the readily available off-the-shelf cationic polymer, 25-kDa branched polyethylenimine (bPEI25). Transfection efficiency of cationic polymers varies among cell lines and is highly dependent on the conditions and environment in which complexes are formed. Factors requiring optimization include the salt concentration, volume, incubation time, mixing order and ratio of polymer to DNA. In this transfection protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
96
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 39 publications
4
96
2
Order By: Relevance
“…The ability of PEI to deliver DNA and siRNA both in vitro and in vivo was reported recently. [22][23][24] Our transfection experiment with PEI70-DNA demonstrated that similar transfection efficiency as with Lipofectamine 2000 can be obtained while lowering cytotoxicity. The influence of N/P ratio of PEI to DNA and varying hydrolysis percentages of PEtOx was explored.…”
Section: Discussionmentioning
confidence: 89%
“…The ability of PEI to deliver DNA and siRNA both in vitro and in vivo was reported recently. [22][23][24] Our transfection experiment with PEI70-DNA demonstrated that similar transfection efficiency as with Lipofectamine 2000 can be obtained while lowering cytotoxicity. The influence of N/P ratio of PEI to DNA and varying hydrolysis percentages of PEtOx was explored.…”
Section: Discussionmentioning
confidence: 89%
“…In a reported case, the authors showed an optimized protocol for more efficient transfection of adherent primary mammalian cells using 25 kDa branched PEI. 12 In this study, the modified method was applicable for, at least, PEI and liposome to deliver genes into a wider range of cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…In general, complexes may undergo physicochemical changes when mixed at different concentrations, and the aggregation of particles may also be influenced by the different ionic strength in the medium. 12,35 The complexation of pDNA/material particle was formed in 700 μL solution for the modified transfection while in 500 μL and then diluted to 2,500 μL system for standard transfection, leading to a different particle concentration and size. Altogether, the change of cellular endocytosis pathway, decrease of particle size, and increase of particle concentration made the modified transfection method a potent tool for nonviral material-mediated gene delivery into a wide range of cell strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to viral vectors, non-viral transfection methods such as electroporation, calcium phosphate (CaPO 4 ) co-precipitation, lipoplex and polyplexmediated methods have been benefited in gaining regulatory clearance and thus preferred for therapeutic protein production as well as for gene therapy [6] . However, these non-viral methods vary with respect to transfection efficiency (Table 1) [7][8][9][10][11] and production cost. Thus, it is important to select an appropriate transfection method, which will be highly efficient and economic.…”
mentioning
confidence: 99%